Improving the Quality of Learning Organizations through School Effectiveness - Salabi, Agus Salim; Muadin, Akhmad; Prasetyo, Muhammad Anggung Manumanoso (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This study aims to investigate how educational institution managers encounter challenges in managing learning organization values and the reasons for these challenges. This qualitative case study aimed to apply knowledge of educational institutions and organizational development by implementing an integrated educational management design process and a learning organization. The investigation was conducted at the Sukma Bangsa School in Lhokseumawe. The case study method was used in this qualitative study, with analysis focused on the integrative design of organizational development in the context of educational management and learning organizations. A culture of strict discipline is deeply ingrained in both the fluidity of the fast-paced workplace and academic achievements. The findings of this study outline the following technical steps involved in the implementation of a learning school program: (1) the effectiveness of the leadership; (2) an understanding of the situation and the formulation of policies; (3) an alignment of the organizational structure and the logic of the program; (4) the prioritization of activities; (5) work that is both practical and reflective; (6) the development of organizational learning capabilities; and (7) the integration of organizational learning capabilities. In a nutshell, the findings indicate that implementing the concept of a learning organization ensures the organization's continued viability and the improvement of its educational offerings. The principles outline how research on the design, implementation, and evaluation of organizational interventions can be conducted to maximize the impact of those interventions in both the real world and the scientific community.